The Effect of Dietary Alpinia officinarum (Hance) Supplementation in Bovns-type Chicks - Seddeag, Mawahib; Madawe, Gadallah; El Badwi, S.M.A.; Bakhiet, A.O. (International Journal of Poultry Science, 2010)
The galangal (the rhizome of Alpinia officinarum, Hance) is popular as a traditional herbal medicine. The present study investigates the effect of diet containing 2%, 5% and 10 % of A. officinarum (Hance) on the biochemical, haematological and histological parameters in Bovans-type chicks treated for 4 weeks. The body weight of the chicks revealed that feeding levels of 2, 5 and 10% dietary A. officinarum was significantly decreased (p<0.05 - 0.01) compared to the control chicks. Significant changes were observed in the activities of AST and ALT and the concentration of total protein, uric acid, albumin and globulin and cholesterol levels. Mild degenerative changes were observed in the liver and kidneys of chicks while no significant differences were recorded in haematological parameters.